Comparison of Bacterial Contamination Before and After Sterilization with UV, Fogging, and Drymist in University Outpatient Dental Hospital - Andriyanto, Arif; Solikhah, Solikhah; Suryani, Dyah; Dedy Kusuma Yulianto, Heribertus (Universitas Airlangga, 2025)
Introduction: Microbial contamination in healthcare facilities, particularly in outpatient rooms, raises the risk of nosocomial infections and endangers the health of both patients and personnel. The purpose of this study is to compare the efficacy of three sterilizing methods—ultraviolet (UV) light, fogging, and drymist—in lowering bacterial counts and microbial species in university outpatient dental hospital. Methods: This study uses a quasi-experimental design with a one-group pretest-posttest procedure. This design involves assessing outcomes before and after sterilization in the same group to evaluate the intervention’s effects. Samples were collected before and after the sterilization process. Sterile swabs were used to gather microbial samples from surfaces such as examination tables, walls, and medical equipment within the outpatient area. The data were analyzed using paired t-tests and ANOVA. Results and Discussion: All three sterilizing methods were effective in lowering microbial counts, with the UV approach showing the greatest decrease (83.9%), followed by drymist (79.6%) and fogging (63.4%). However, ANOVA findings revealed no significant difference in effectiveness across the three techniques (p = 0.979). Nonetheless, certain bacterial species that are more resistant to sterilization survived after treatment. Conclusion: UV, fogging, and dry mist sterilizing technologies reduce microbial counts in comparable ways, although their performance may be impacted by ambient conditions and the types of bacteria presents. A mix of sterilizing procedures may be required for best results.